Forgeries of the Seals of the Kalmyk Rulers - Bembya L. Mitruev (Монголоведение)
Introduction. In recent years, there have been publications in which letters of the Kalmyk khans and the highest nobility, including prints of their seals, have been published, which undoubtedly attracts the attention of researchers. These seals, as well as other seals, the impressions of which have been preserved on archival documents, are interesting as monuments of the political history of the Kalmyk people. Until recently, the fact of the existence of forged seals of the Kalmyk Khan Ayuka, his heir Chagdordzhab and the owner of Lubzha remained unknown. The purpose of the article is to introduce into scientific circulation sphragistic data on forgeries of seals of Ayuka, Chagdordzhab and Lubji. The material for the study was the business correspondence of Ayuka Khan, Chakdordzhab and the owner of the Puddle, dated the 18th century. Results. The study presents data on three forgeries of the seals of the representatives of the Kalmyk nobility. All three forgeries were apparently used for some reason due to the absence of the access to the original seal. And if the first fake clearly gives itself away with a different technique, then the second and third are like mirror images of the originals. All three forgeries of the seals were used by representatives of the highest nobility: the wives of Khan Ayuka and his heir Chagdordzhab, as well as the grandson of Dorzhi Nazarov (a pretender to the throne in the Kalmyk Khanate after the death of Khan Ayuka in 1724). The reason for the use of fakes is unclear, the most likely option is that there was no possibility of using the original seal.